Introduction to Philosophy Aesthetic Theory and Practice - Saito , Yuriko; Sonderegger , Ruth; Kleesattel , Ines (Open textbook library., 2021)
Aesthetic Theory and Practice offers fresh perspectives on canonical and emerging topics in aesthetics, and also brings attention to a number of culturally sensitive topics that are customarily silenced in introductions to philosophical aesthetics. The papers are heterogeneous in terms of length and degrees of difficulty, inviting the reader into the study of contemporary aesthetics, which spans a lifetime.